CN bond formation via palladium-catalyzed carbene insertion into NN bonds: inhibiting the general 1, 2-migration process of ylide intermediates. Issue 18 (15th February 2017) - Zhu, Chuanle; Chen, Pengquan; Zhu, Rui; Lin, Zhiming; Wu, Wanqing; Jiang, Huanfeng
Abstract : Inhibiting the general 1, 2-migration process of ylide intermediates, a new palladium-catalyzed carbene insertion into NN bonds affords various N, N -disubstituted hydrazones. Abstract : A new example of CN double bond formation in metal carbene insertion reactions is reported. Remarkably, the general 1, 2-migration process of the corresponding ylide intermediates in X–H carbene insertion reactions that leads to C–X single bond formation is completely inhibited by replacing the H atom with a nitrogen atom. This palladium-catalyzed carbene insertion reaction with NN double bonds gave various N, N -disubstituted hydrazone products in high yields.